Preparation of barium/lanthanum doped PZT perovskites and assessment of their photocatalytic activity (Revista de Investigaciones Universidad del Quindío, 2013)
In this work, preliminary results about the photocatalytic activity of ABO3 perovskite semiconductors of the type Pb1-xRxZr0,40Ti0,60O3 (R=La,Ba) are presented. The materials were prepared by the sol-gel method by varying x in the range 0, 0.5 and 1.0; complex, high-purity ceramic oxides were obtained with controlled stoichiometry. The materials were employed as active photocatalysts in the degradation of methylene blue, a contaminant frequently found in textile wastewaters. All the perovskites exhibited 80% of decolourization in the range of 120 min. The photocatalytic activity was favored by the presence of doping agents under UV irradiation.
Keywords: Sol-gel, perovskita; Pb1-xRxZr0,40Ti0,60O3(R=La,Ba); photocatalysis; methylene blue